Fuzzy Stability of an n-Dimensional Quadratic and Additive Functional Equation - Yang Hi Lee; Soon-Mo Jung (Advances in Fuzzy Systems)
We will investigate a fuzzy version of stability for the functional equation 2f(∑i=1nxi)+∑1≤i,j≤n,i≠jf(xi-xj)=(n+1)∑i=1nf(xi)+(n-1)∑i=1nf(-xi) in the sense of Mirmostafaee and Moslehian.